IMPROVEMENT STRATEGY OF EARLY CHILDHOOD LANGUAGE DEVELOPMENT THROUGH THE ROLE PLAYING METHODS IN MACRO PLAY CENTER AT RA. BAITUSSALAM CIMAHI - Erika Rufaidah (Empowerment : Jurnal Ilmiah Program Studi Pendidikan Luar Sekolah, 2018)
Abstract Development of Early Childhood Education (PAUD) learning includes the field of developing behavioral formation and the field of developing basic skills. The field of developing behavioral formation includes religious and moral and social emotional values. While the development of basic abilities includes language, cognitive, and physical or motoric abilities. One area of basic development that needs to be developed  is language development. Language skills are important because speaking with children will express their desires and can communicate with others around them. Language is an expression of mind and knowledge when children will interact with others. Children who are growing and developing communicate the needs of their thoughts and feelings through language, The objectives of this research are: (1) Describe the planning strategy to improve the development of early childhood language through the role playing method in the macro play center. (2) Describe the implementation of strategies to improve the development of early childhood language through the role playing method in the macro play center. (3) Describe the evaluation of strategies to improve the development of early childhood language through the role playing method in the macro play center. (4) Describe the results of strategies to improve the development of early childhood language through role playing methods in the macro play center. Learning methods that can be used to help improve children's language development are through the role playing method in the macro play center. With the role playing method in the macro play center, it is hoped that the development of children's language will be improved.Keywords: Language Development, Early Childhood, Macro Play Center